2022
DOI: 10.1111/fcp.12826
|View full text |Cite
|
Sign up to set email alerts
|

Is lithium neuroprotective? An updated mechanistic illustrated review

Abstract: Neurodegeneration is a pathological process characterized by progressive neuronal impairment, dysfunction, and loss due to mitochondrial dysfunction, oxidative stress, inflammation, and apoptosis. Many studies have shown that lithium protects against neurodegeneration. Herein, we summarize recent clinical and laboratory studies on the neuroprotective effects of lithium against neurodegeneration and its potential to modulate mitochondrial dysfunction, oxidative stress, inflammation, and apoptosis. Recent findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 245 publications
0
6
0
Order By: Relevance
“…However, whether TREM2 also has neuroprotective effects after TBI has not yet been elucidated. The protein kinase B (Akt)/cAMP-responsive element-binding protein (CREB)/brain-derived neurotrophic factor (BDNF) axis has been proven to have neuroprotective effects against neurodegeneration by preventing neuroinflammation, oxidative stress, apoptosis, and mitochondrial dysfunction [ 30 ]. In addition, this signalling pathway can alleviate critical illness-related corticosteroid insufficiency after TBI by promoting neuronal survival [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, whether TREM2 also has neuroprotective effects after TBI has not yet been elucidated. The protein kinase B (Akt)/cAMP-responsive element-binding protein (CREB)/brain-derived neurotrophic factor (BDNF) axis has been proven to have neuroprotective effects against neurodegeneration by preventing neuroinflammation, oxidative stress, apoptosis, and mitochondrial dysfunction [ 30 ]. In addition, this signalling pathway can alleviate critical illness-related corticosteroid insufficiency after TBI by promoting neuronal survival [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, low-dose lithium has been found to protect against mild cognitive impairment (MCI) and dementia by increasing the GMV 91 , 92 . A review showed that lithium increases the GMV by preventing inflammation, oxidative stress, apoptosis, and mitochondrial dysfunction via the phosphatidylinositol-3 (PI3)/Akt/GSK-3β and PI3/Akt/cAMP response element-binding protein/brain-derived neurotrophic factor signaling pathways 93 . Our results are inconsistent with these findings, as regional GMV increases did not overcome the reduction of the whole-brain GMV.…”
Section: Discussionmentioning
confidence: 99%
“…Lithium activates both the PI3K/AKT/CREB pathway and the cAMP/PKA/CREB pathway, leading to increased production of BDNF. This activation inhibits oxidative stress, inflammation, and apoptosis, achieving neuroprotective effects 97 . Additionally, the inhibition of GSK-3β/CREB/BDNF 98 and MAPK/ERK/CREB/BDNF 73 signaling pathways can upregulate BDNF expression, thereby alleviating cerebral ischemia-reperfusion injury.…”
Section: Molecular Mechanismmentioning
confidence: 99%